Ethnic Disparities and Incidence of Postoperative Complications in Obese Patients Undergoing Total Knee Arthroplasty: Analysis of the American College of Surgeons National Surgical Quality Improvement Program Data Set. Issue 23 (1st December 2021) - Alfaro, Robert; Kinter, Kevin; Mihas, Alexander; Castro, Grettel; Rodriguez, Pura; Zevallos, Juan; Elkbuli, Adel; Barengo, Noel; Ruiz-Pelaez, Juan
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Total knee arthroplasty (TKA) is common but complex operation. A paucity of literature exists on differences between Hispanics and non-Hispanics with TKA. Our study aims to investigate the association between Hispanic ethnicity and complications in obese patients undergoing TKA. Methods: This is a retrospective cohort study using the National Surgical Quality Improvement Program database for patients with body mass index ≥30 kg/m 2 who underwent TKA. Exposure in this study was ethnicity (Hispanic versus non-Hispanic), and the primary outcome was postoperative complications. Associations between ethnicity and baseline characteristics and between covariates and the outcome were assessed via bivariate analysis. Multiple logistic regression was done to determine associations between Hispanic ethnicity and complications while controlling for confounders. Results: Thirty five thousand twenty-seven patients were included in our study, of which 6.3% were Hispanic. Among obese adults, Hispanics had a 1.24 (95% CI 1.11 to 1.39) times greater odds of having a postoperative complication after TKA than non-Hispanics. This increased to 1.36 (95% CI 1.20 to 1.54) after adjusting for confounders. Hispanics were notably more likely to receive transfusion (2.62% vs. 1.59%, P < 0.001) and have prolonged length of stay (13.29% vs. 11.12%, P = 0.002) but were less likely to have wound disruption (0.05% vs. 0.27%, P = 0.042). Conclusion: In a national database, Hispanic ethnicity was associated with greater odds of postoperative complication in obese patients undergoing TKA compared with non-Hispanics. Future studies focusing on a wide range metrics of social determinants of health are needed to further investigate barriers and intervention to eliminate racial/ethnic disparities in surgical patients.